Pengaruh Return On Assets, Earning Per Share Dan Total Assets Turn Over Terhadap Dividend Payout Ratio Pada PT Kalbe Farma Tbk Periode 2013-2023 - Syafaaiska Titania Ayodia; Vidya Amalia Rismanty (CV. KAMPUS AKADEMIK PUBLISING, 2025)
From 2013 to 2023 the company PT Kalbe Farma Tbk which is a pharmaceutical company in Indonesia has experienced fluctuations in its financial performance. The number of competitors that have emerged requires PT Kalbe Farma Tbk to maintain the company's financial stability. This study aims to analyze the partial and simultaneous influence between Return On Assets (ROA), Earning Per Share (EPS), Total Assets Turn Over (TATO) which affects the Dividend Payout Ratio (DPR) at PT Kalbe Farma Tbk for the period 2013-2023. The method used in this research is quantitative method. The research population used in this study were all financial statements of PT Kalbe Farma Tbk for the period 2014-2023. research samples were obtained using purposive sampling technique with the criteria of complete financial statements such as income statements, statements of financial position, and cash flow statements during the study period. The data analysis technique used is statistical analysis, classical assumption test which includes normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. In addition, this study uses the Coefficient of Determination Test (R2), multiple linear regression analysis. Furthermore, hypothesis testing uses t-test, F-test which is assisted by the IBM SPSS Statistics program version 29. The results showed that ROA, and TATO partially had a significant effect on DPR, while EPS partially had no effect on DPR. The results of simultaneous research between ROA, EPS and TATO show that together they have an effect on DPR